Gender Equality in the Workplace: Challenges and Progress in the 21st Century - Shujaat Yousuf pirzada (CV. Radja Publika, 2025)
Gender equality in the workplace remains a central issue in the global discourse on human rights and inclusive development. Despite progress in education and employment participation, significant gender disparities persist in wages, leadership representation, occupational roles, and access to opportunities. This research paper explores the major challenges to achieving gender equality at work, such as the gender pay gap, occupational segregation, underrepresentation in leadership positions, and the unequal burden of unpaid care work. It also highlights notable progress made in the 21st century, including legal reforms, corporate diversity programs, and supportive policies for working women. The paper concludes by offering strategic recommendations to accelerate progress, emphasizing the importance of systemic change, inclusive practices, and cultural transformation in achieving gender-equal workplaces.